Deconstruction of maleficent characters in the movie titled 'maleficent' - Widyahening, Ch. Evy Tri; Wardhani, Nugraheni Eko (Linguistics and Culture Review, 2021)
The purpose of this study was to analyze 1) Maleficent character deconstruction, 2) female image deconstruction in the story, and 3) character values ??contained in the studied films. The research method used is a qualitative method with an emphasis on the character of Maleficent. Data collection techniques used are literature study techniques or documentation studies. The data analysis technique analyzes the content or text-based deconstruction survey theory, which begins with selecting data from the rewatching film 'Maleficent' and the rereading of the Sleeping Beauty fairy tale. The idea was used to search for opposition binaries and analyze Maleficent's character both in the film and in the original fairy tale. The results showed that Maleficent's existence was deconstructed into a figure of a magic woman who was kind, compassionate, motherly and always maintained the calm and safety of Princess Aurora. Deconstruction takes place on other supporting characters in evil films, such as the king and princess Aurora. The deconstruction can be seen in the image of women depicted in the film. Princess Aurora's image is deconstructed into a vital, assertive, straightforward, brave, and critical figure.